COST OF GOODS SOLD OF WAJIK AT CAP KUDA TERBANG SMALL AND MEDIUM ENTERPRISE IN BLITAR: AN ANALYSIS - Suprianto Suprianto; Diana Elvianita Martanti (Universitas Islam Balitar, 2020)
The purpose of this research was to determine the calculation of cost of goods sold of Wajik at Mrs. Sulasmi’s Cap Kuda Terbang Small and Medium Enterprise (UKM) in Kademangan, Blitar Regency. This research was carried out to figure out how to determine the selling price of Wajik, and to analyze whether the selling price was appropriate. The research method used in this research was qualitative approach so that it can develop and obtain in-depth findings. Data were obtained through interviews and observations. The data of interview and observation were subsequently analyzed to find out how to determine the selling price of Wajik at UKM Cap Kuda Terbang, and to analyze whether the prize has yet to be approriate. The technique used to check the validity of the data was the triangulation technique. Findings show that the cost of goods sold based on full costing method was higher than the cost of goods sold calculated by the company; it appears that there are differences in the calculation of cost of goods sold according to the company after being evaluated.